Witnessing and Remembering Trauma in Northeast Asia in the Visual Age. Issue 3 (3rd July 2022) - Kal, Hong; Rhee, Jooyeon
ABSTRACT: This Special Issue is a collaborative attempt by scholars of visual arts, cultural history and literature to contribute to the uncovering of symbolic and materialistic meanings and effects of visual art and media that address urgent issues in the lives of many people in Northeast Asia. Its first goal is to establish the context in which art makers are positioned and to discuss how their memory and post-memory of disasters shape the content of their works. Second, it explores the potential and limits of visual works to witness and remember physical and psychological trauma caused by the disasters. The third goal is to shed light on the ethical concerns surrounding the visual representation of disasters and victims. Its final goal is to explore how these artworks are grounded in the shared history of Northeast Asia during 'the visual age'.